PENENTUAN NILAI “SUN PROTECTION FACTOR” ( SPF ) SEDIAAN LOTION YANG MENGANDUNG KOMBINASI EKSTRAK DAUN KELOR DENGAN RIMPANG BANGLE SEBAGAI TABIR SURYA - Jumain Jumain; Tajuddin Abdullah; Asmawati Asmawati (Jurusan Farmasi Politeknik Kesehatan Makassar, Kementerian Kesehatan RI, 2021)
Determination Of The SPF (Sun Protection Factor) Value For Lotions Containing A Combination Of Moringa Leaf Extract And Bangle Rhizome As Sunscreen The development of sunscreens with natural ingredients is generally accepted by the public hence, it is necessary to develop sunscreen lotions from natural ingredients such as a combination of Moringa Leaves and Bangle Rhizome. This research aims to determine the